Pengelolaan Pajak Di Industri Food And Beverage: Peran Fixed Asset Intensity, Corporate Governance, dan Corporate Social Responsibility - Iqbal M. Aris Ali; Sulastri Surita (Program Studi Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2024)
The purpose of this research is to analyze the effect of fixed asset intensity, Corporate Governance and Corporate Social Responsibility on tax management. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample in this study were 76 companies, which were taken using a purposive sampling technique. The statistical test tool used is panel data regression analysis using eviews. The results of this study found that the Board of Commissioners has a positive effect on tax management while the Intensity of Fixed Assets, Independent Commissioners, Board of Commissioners and Directors Compensation, and Corporate Social Responsibility have no effect on tax management.